Housing affordability, public policy and economic dynamics: An analysis of the city of Lisbon - Miguel Lorga; Jo\~ao Fragoso Januário; Carlos Oliveira Cruz (Journal of Risk and Financial Management, 2022)
The increasing growth of population living in cities, associated with the commoditization of investment in real estate, has impacted real estate prices and created obstacles for average income families to meet their housing needs. This problem is generalized to virtually all cities, but it has assumed larger proportions in cities where economic activities (tourism, financial services, high-tech industry) have flourished after the financial crisis. Lisbon is one of those cases. The growth of short-term rentals led to an increase in the property prices well above the average income growth, eroding housing affordability. This paper will focus on analyzing Lisbon's affordability and understanding its main determinants. The analysis is carried out from the compilation and processing of data from 2004 to 2019, in the context of the municipality of Lisbon, using statistical instruments of linear regression in an exploratory and predictive approach. The results suggest a great influence of factors such as tourism, the foreign population with resident status, the propagation of short-term rentals and public policies on the worsening of housing affordability. In view of these conclusions, the preponderance of the type of public policies implemented and their relationship with the most prominent factors on housing affordability is debated.
Keywords: 650; affordability; housing; Lisbon; real estate